Evaluation of Risk Factors for Carcinoma Breast in Pakistani Women (Journal of Fatima Jinnah Medical University, 2018)
Objective: To evaluate the risk factors for breast cancer in women attending OPD Breast Clinic, Sir Ganga Ram Hospital, Lahore and compare the local with the western risk factors.Method: A cross-sectional study was conducted at OPD Breast Clinic from January 2008 to June 2013. A total of 200 females were included. Diagnosis of breast cancer was based on histopathological findings. Age at presentation, stage and type of carcinoma breast, age at menarche, age at menopause, marital status, age at first full term pregnancy, parity, breast feeding history (12 months at least), use of oral contraceptives (regular uptake for at least one year), family history of breast cancer and other cancers (first degree relatives), smoking (20 pack years), were evaluated as risk factors for breast cancer. Demographic data and information related to risk factor were collected employing a short structured proforma.Results: The mean age of diagnosis was 45 years. Presentation at advanced stage was most common (61%) and Invasive Ductal CA was the most common type (95%). 99% of the patients were married, 93% parous, and 96% patients had age 30. Family history of breast cancer was +ve in 12% of patients and 13% of patients had first degree relatives affected from other types of cancer.Conclusion: In Pakistan, the females presents with breast cancer at a younger age (
Keywords: Breast cancer, risk factors